Incidence of bifurcations in mandibular incisors - Madeira, Miguel C.; Hetem, Sebastião (Elsevier, 1973)
An anatomic study of the mandibular incisor root canal has been performed to determine the incidence of complete and incomplete bifurcations. © 1973.